(*)ABA in Germanic verbs. Issue 1 (20th November 2018) - Andersson, Samuel
Abstract : This paper discusses cases where non-adjacent cells in morphological paradigms are syncretic, commonly called ABA patterns (Bobaljik 2012 et seqq. ). Data from verbs in Germanic languages are examined, as earlier work suggests that a *ABA constraint may be active in this domain. It will be shown that there are verbs in several Germanic languages which exhibit genuine ABA patterns, precluding an analysis based on a constraint *ABA. It is suggested that the rarity of ABA patterns should instead be given a diachronic explanation in terms of Proto-Germanic conjugation classes. This approach is independently motivated by frequency asymmetries in modern Germanic languages, and correctly predicts where ABA patterns are more likely to appear. The research reported here adds to a rapidly-growing body of work on extralinguistic explanations for linguistic patterns (Anderson 2016 ), suggesting a severely reduced explanatory role for formal linguistic constraints.